Respuesta :
y=a (x-h)^2+k
y=a (x-3)^2+(-12)
plug in your point (0,6)
6=a (0-3)^2-12
6=a (9)-12
6=a (9) also seen as
6= 9a-12
now add 12 on both sides
18=9a
divide
2=a
y=2 (x-3)^2-12
y=a (x-3)^2+(-12)
plug in your point (0,6)
6=a (0-3)^2-12
6=a (9)-12
6=a (9) also seen as
6= 9a-12
now add 12 on both sides
18=9a
divide
2=a
y=2 (x-3)^2-12
Answer:
[tex]y=2(x-3)^2-12[/tex]
Step-by-step explanation:
The vertex form of a parabola is
[tex]y=a(x-h)^2+k[/tex] ...(i)
where, a is a constant and (h,k) is vertex.
It is given that vertex of the parabola is (3,-12).
Substitute h=3 and k=-12 in equation (i).
[tex]y=a(x-(3))^2+(-12)[/tex]
[tex]y=a(x-3)^2-12[/tex] ...(ii)
It is given that the parabola passes through the point (0,6). It means the equation of parabola must be true for (0,6).
Substitute x=0 and y=6 in equation (ii).
[tex]6=a(0-3)^2-12[/tex]
[tex]6+12=9a[/tex]
[tex]18=9a[/tex]
[tex]2=a[/tex]
Substitute a=2 in equation (ii).
[tex]y=2(x-3)^2-12[/tex]
Therefore, the equation of parabola is [tex]y=2(x-3)^2-12[/tex].